Legal Status of Transmigration Land Which Has Been Auctioned By The State Assets Service Office and Auction Until The Certificate is Issued - Sumeru, Fayuthika Alifia Kirana; Tjempaka Tjempaka (JURNAL USM LAW REVIEW, 2025)
This study aims to examine the legal status of land rights that can be owned by transmigration communities and the legal protection that can be taken by the community if they feel disadvantaged. The research method used is normative legal research using a statutory approach and a case approach. The government is holding a transmigration program for population equality throughout Indonesia, therefore, a transmigration area was formed as a residential area and a place of business for the community to improve the community's standard of living. Over time, the need for land has increased because community growth is not comparable to the available land, so it often causes disputes. One example of a land dispute that occurs is transmigration land owned by the community that has changed ownership to company land, where the transmigration land owned by the company was obtained by winning an auction. This study was conducted to determine the appropriate legal system in resolving transmigration land disputes whose land is used as an auction object, as well as to find out about the legal protection received by transmigration communities. The results of the study are that the legal status of transmigration land that is used as an auction object should still belong to the transmigration community because transmigration land cannot be transferred, while legal protection for transmigration communities should mean that the land is not used as an auction object by the local government because it still belongs to the transmigration community.